2018
DOI: 10.1002/qj.3218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diurnal variation of GPM IMERG‐derived summer precipitation over the contiguous US using MRMS data

Abstract: Precipitation Measurement (GPM), which provides merged microwave and infrared satellite precipitation estimates, over the contiguous US. The study focuses on diurnal variations in precipitation during a two-year summer period (June-August, 2014-2015). The normalized amplitude and phase of the diurnal cycle of IMERG are evaluated against those of ground reference from the Multi-Radar/Multi-Sensor system in terms of precipitation amount, frequency and intensity on a 1 • /1 h scale. IMERG well captures large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 56 publications
8
42
0
Order By: Relevance
“…It might be associated with infrared sensors F I G U R E 2 Comparison of mean monthly precipitation (mm per month) for different datasets (symbols) across all grids of Karun basin (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Red lines denote datasets which did not employ gauge data, while blue lines indicate datasets which use some gauge records, and turquoise lines refer to datasets which extensively used gauge observations T A B L E 2 Statistical measures of the evaluated monthly datasets over Karun basin (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) Group Dataset having difficulties to detect warm cloud process especially over mountains (Dinku et al, 2018;O and Kirstetter, 2018). The underestimation in SM2RAIN-CCI could be related to the fact that once the surface soil is saturated after intense or long-lasting precipitation events, no additional increase is possible such that no additional precipitation can be deduced from the soil moisture data (Brocca et al, 2013).…”
Section: All-basin Summary Evaluation Of Precipitation Productsmentioning
confidence: 99%
“…It might be associated with infrared sensors F I G U R E 2 Comparison of mean monthly precipitation (mm per month) for different datasets (symbols) across all grids of Karun basin (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Red lines denote datasets which did not employ gauge data, while blue lines indicate datasets which use some gauge records, and turquoise lines refer to datasets which extensively used gauge observations T A B L E 2 Statistical measures of the evaluated monthly datasets over Karun basin (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) Group Dataset having difficulties to detect warm cloud process especially over mountains (Dinku et al, 2018;O and Kirstetter, 2018). The underestimation in SM2RAIN-CCI could be related to the fact that once the surface soil is saturated after intense or long-lasting precipitation events, no additional increase is possible such that no additional precipitation can be deduced from the soil moisture data (Brocca et al, 2013).…”
Section: All-basin Summary Evaluation Of Precipitation Productsmentioning
confidence: 99%
“…More details can be found in the following articles and references within [42][43][44][45][46]. It should be mentioned that several studies [47][48][49] have indicated an overestimation of IMERG products in the estimated precipitation under heavy rainfall events.…”
Section: Data Usedmentioning
confidence: 99%
“…High spatial and temporal resolution satellite precipitation products, such as IMERG, offer an unprecedented opportunity to investigate the diurnal cycle. Reference [42] showed that the 30-min temporal resolution IMERG well captures the diurnal and semidiurnal precipitation patterns identified by Fig. 6.…”
Section: B Diurnal Cyclementioning
confidence: 97%
“…In a parallel study [43], we have analyzed the diurnal cycle across the globe using four years of IMERG data (June 2014-May 2018); for each 5 • lat/lon grid box, precipitation occurrence, amount (mean precipitation, including zero values), and intensity (the conditional mean for precipitation >0 mm/h) have been computed at half-hour resolution. These histograms have been fit by diurnal and semidiurnal harmonic functions with a least-squared-error method [42], weighted by their random errors [43]. The importance of the diurnal and semidiurnal cycles has been then evaluated by looking at the amplitudes of the corresponding harmonics, whereas the position of the maximum in the diurnal harmonic provides the timing of the peak.…”
Section: B Diurnal Cyclementioning
confidence: 99%